Reliability Predictors in Narratives of Oocyte Donors - Plotnikova, Maria V.; Polyakova, Irina G. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
This article analyses protocols of in-depth interviews of oocyte donors using a comprehensive methodology that combines aspects of psychology, semiotics, pragmatics, and cognitive linguistics. The authors examine discursive markers of oral dialogic speech that indirectly indicate the reliability of the statements of the interviewees or their desire to disguise information during the conversation. The interdisciplinary nature of the study is provided by the synthesis of psychological and linguistic methodological approaches to the analysis of linguistic material, united around the logical-philosophical category of modality. A similar methodological approach is found in the authorial methods of criteria analysis by A. Vrij. Within the framework of the first method, the authors consider the cognitive operations transmitted by the interviewee while describing the ongoing events, as well as the structural and lexical-semantic makeup of the text as indicators of the reliability of the information presented, which corresponds to the linguistic interpretation of modality. The second method of analysis is developed to a greater extent in line with the psychological approach to the definition of modality: the presence of accurate sensory information in the narrative of the interviewees is a significant indicator of the speaker’s truthfulness. The analysis of interviews with oocyte donors using these methods reveals that perceptual and affective information updated in a communication situation is more indicative of the truthfulness of the speaker than the mental representation of the events and facts presented. In addition, truth-tellers provide more detail, also related to the realm of sensory perception. The desire to disguise any information is often accompanied by a reference to forgetfulness and a transition to another topic of the storyline. The applied research results may be of interest to a wide range of interviewers on different topics while the scholarly results can be used in interdisciplinary art and social science studies.